Last Bus to Wisdom (Two Medicine Country, ,, 2016)
"In the spirit of The Bartender's Tale, a lively and poignant coming-of-age story about a boy and his great-uncle on a cross-country odyssey. Donal Cameron is being raised by his grandmother, the cook at the legendary Double W ranch in Doig's beloved Two Medicine Country of the Montana Rockies, a landscape that gives full rein to an eleven-year-old's imagination. But when Gram has to have surgery for "female trouble" in the summer of 1951, all she can think to do is to ship Donal off to her sister in faraway Manitowoc, Wisconsin. There Donal is in for a rude surprise: Aunt Kate, bossy, opinionated, argumentative, and tyrannical, is nothing like her sister. She henpecks her good-natured husband, Herman the German (as Donal discovers him to be), and Donal can't seem to get on her good side either. After one contretemps too many, Kate decides to pack him back to the authorities in Montana on the next Greyhound. But to Donal's surprise, he's not traveling solo: Herman the German has decided to fly the coop with him. In the immortal American tradition, the pair light out for the territory together, meeting a classic Doigian ensemble of characters and having rollicking misadventures along the way. Charming, wise, and slyly funny, Last Bus to Wisdom is another treasure of a novel from the best storyteller of the West" --

The Kite Runner (Simon & Schuster Audio, Recorded Books, Audioworks, Riverhead Books, Penguin Publishing Group, Simon & Schuster, 2004)
The 10th anniversary edition of the New York Times bestseller and international classic loved by millions of readers.The unforgettable, heartbreaking story of the unlikely friendship between a wealthy boy and the son of his father's servant, The Kite Runner is a beautifully crafted novel set in a country that is in the process of being destroyed. It is about the power of reading, the price of betrayal, and the possibility of redemption; and an exploration of the power of fathers over sons-their love, their sacrifices, their lies.A sweeping story of family, love, and friendship told against the devastating backdrop of the history of Afghanistan over the last thirty years, The Kite Runner is an unusual and powerful novel that has become a beloved, one-of-a-kind classic.
This is a Playaway. (Playaways are self-contained. battery-operated units)

From the corner of his eye (Bantam Books, Bantam, Books on Tape, bantam Books, 2004)
Bartholomew Lampion is born on a day of tragedy and terror when the lives of everyone in his family are changed forever. On this same day, a ruthless man learns that he has a mortal enemy named Bartholomew and sets out to find him. In San Francisco, a girl is born, her destiny mysteriously linked to the fates of Barty and the man who stalks him. At age three, Barty loses his sight only to regain it ten years later. What happens as his amazing life unfolds results in a breathtaking journey of courage, heart-stopping suspense, and high adventure.

The graduation of Jake Moon (Atheneum Books for Young Readers, 2000)
Fourteen-year-old Jake recalls how he has spent the last four years of his life watching his grandfather descend slowly but surely into the horrors of Alzheimer's disease.

Sudden country (Double D western, ,, 1991)
Description Not Provided

The Fox (Thorndike Press, a part of Gale, a Cengage Company, Penguin Audio, G.P. Putnam's Sons, 2018)
Former chief of the British Secret Intelligence Service Adrian Weston is awoken in the middle of the night by a phone call from the prime minister. Her news is shocking: the Pentagon, the NSA, and the CIA have been hacked simultaneously, their seemingly impenetrable firewalls breached by an unknown enemy known only as "The Fox". Even more surprisingly, the culprit is revealed to be a young British teenager, Luke Jennings. He has no agenda, no secrets, just a blisteringly brilliant mind. Extradition to the US seems likely - until Weston has another idea: If Luke can do this to us, what can he do to our enemies?

Martin Marten: a novel (Thomas Dunne Books, an imprint of St. Martin's Press, Thomas Dunne Books/St. Martin's Press, 2015)
"Dave is fourteen years old, living with his family in a cabin on Oregon's Mount Hood (or as Dave prefers to call it, like the Native Americans once did, Wy'east). He is entering high school, adulthood on the horizon not far off in distance, and contemplating a future away from his mother, father, and his precocious younger sister. And Dave is not the only one approaching adulthood and its freedoms on Wy'east that summer. Martin, a pine marten (a small animal of the deep woods, of the otter/mink family), is leaving his own mother and siblings and setting off on his own as well. As Martin and Dave's paths cross on forest trails and rocky mountaintops, they and we witness the full, unknowable breadth and vast sweep of life, and the awe inspiring interconnectedness of the world and its many inhabitants, human and otherwise. Martin Marten is a coming of age tale like no other, told in Brian Doyle's joyous, rollicking style"--

The adventures of Huckleberry Finn (Classic collection), ,, 2011)
Called "the veriest trash" by a member of the Concord, Massachusetts Library Board that banned the novel when it was first published, Huckleberry Finn has come to be viewed, as H.L. Mencken put it, as "one of the great masterpieces of the world." Ernest Hemingway wrote that "All modern American literature comes from one book by Mark Twain called Huckleberry Finn....There was nothing before. There has been nothing as good since." A daringly ironic attack on racism American-style, Twain's story of what he once called a "sound heart" triumphing over a "deformed conscience" is poignant, powerful, and fresh. It is no wonder that this extraordinary book continues to captivate readers around the world. This handsome Oxford World's Classic edition uses the reliable 1885 text and includes in-depth, up-to-date editorial apparatus
Discover Moses and the bulrushers , Our gang's dark oath , We ambuscade the A-rabs , Hair-ball oracle , Pap starts in on a new life , Pap struggles with the Death Angel , I fool Pap and get away , I spare Miss Watson's Jim , House of death floats by , What comes of handlin snake-skin? , They're after us! , "Better let blame well alone" , Honest loot from the "Walter Scott" , Was Solomon wise? , Fooling poor old Jim , Rattlesnake-skin does its work , Grangerfords take me in , Why Harney rode away for his hat , Duke and the Dauphin come aboard , What royalty did to Parkville , Arkansaw difficulty , Why the lynching bee failed , Orneriness of kings , King turns parson , All full of tears and flapdoodle , I steal the king's plunder , Dead Peter has his gold , Overreaching don't pay , I light out in the storm , Gold saves the thieves , You can't pray a lie , I have a new name , Pitiful ending of royalty , We cheer up Jim , Dark, deep-laid plans , Trying to help Jim , Jim gets his witch pie , "Here a captive heart busted" , Tom writes nonnamous letters , Mixed-up and splendid rescue , "Must 'a' been sperits" , Why the didn't hang Jim , Last. Nothing more to write.

The karate class mystery (Invisible Inc, ,, 1996)
When someone takes Justin's karate belt, his friends in Invisible Inc. try to determine a motive as they investigate the mystery.

The buffalo soldier: a novel (Shaye Areheart Books, 2002)
After losing their twin daughters in a flash flood, a grief-stricken couple take in a foster child

Flying crows: a novel (Random House, 2004)
Description Not Provided

Compulsion: a novel (Frank Clevenger novels, 3, 1, 2002)
Description Not Provided